2012
DOI: 10.3109/00365513.2012.725864
|View full text |Cite
|
Sign up to set email alerts
|

Smoking, von Willebrand factor and ADAMTS-13 in healthy males

Abstract: While von Willebrand factor (vWF) has been reported to be elevated in smokers, there are no reports on the effects of smoking on its cleaving protease ADAMTS-13, particularly in subjects of Arab ethnicity. This study was conducted to determine the effects of smoking on vWF and ADAMTS-13 antigen and activity levels in Arab males. Venous blood samples from 80 smoking (at rest) and 80 non-smoking healthy males were collected after asking subjects to fast and refrain from smoking for 8 hours. Similar sampling was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…This finding is consistent with a previous study in Arab males that observed lower ADAMTS13 antigen levels in smokers. 36 The effect of smoking on ADAMTS13 levels was independent of the genetic effects of significant signals at the ADAMTS13 locus. To date the correlation between ADAMTS13 and smoking has not been examined except in extreme deficiencies of ADAMTS13, such as those observed in patients with acute acquired or congenital thrombotic thrombocytopenic purpura.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is consistent with a previous study in Arab males that observed lower ADAMTS13 antigen levels in smokers. 36 The effect of smoking on ADAMTS13 levels was independent of the genetic effects of significant signals at the ADAMTS13 locus. To date the correlation between ADAMTS13 and smoking has not been examined except in extreme deficiencies of ADAMTS13, such as those observed in patients with acute acquired or congenital thrombotic thrombocytopenic purpura.…”
Section: Discussionmentioning
confidence: 96%
“…However, it has been shown that another number of ADAMTS family called ADAMTS-13, whose activity was significantly lower in smokers compared to nonsmokers in healthy subjects. [21] Hyperlipidemia caused by high-fat diet in mice tend to have lower ADAMTS-13 activity. [22] To our surprise, we did not detect significant correlation between plasma lipid levels and ADAMTS-7, although hyperlipidemia history was significantly correlated with ADAMTS-7.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) One study demonstrated that vWF activity is increased in smokers. ( 18 ) One group of authors reported that vWF levels are higher in COPD patients than in healthy subjects; however, smokers without obstruction were not included in that analysis. ( 19 ) Another study demonstrated that serum vWF levels increase in COPD patients during exacerbations.…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ) Um estudo demonstrou que a atividade do FvW encontra-se aumentada em fumantes. ( 18 ) Com relação a pacientes com DPOC, um grupo de autores reportou que o FvW está elevado nesses pacientes quando comparados a indivíduos saudáveis; no entanto, pacientes tabagistas sem obstrução não foram incluídos naquela análise. ( 19 ) Em outro estudo, foi demonstrado que os níveis séricos do FvW aumentam em pacientes com DPOC com exacerbação.…”
Section: Discussionunclassified